MICROSATELLITE LOCI FOR ORTHOPHYTUM OPHIUROIDES (BROMELIOIDEAE, BROMELIACEAE) SPECIES ADAPTED TO NEOTROPICAL ROCK OUTCROPS - Aoki-Goncalves, Felipe; Louzada, Rafael B.; De Souza, Livia Moura; Palma-Silva, Clarisse [UNESP] (Botanical Soc Amer Inc, 2014)
Premise of the study: Microsatellite primers were developed for Orthophytum ophiuroides, a rupicolous bromeliad species endemic to neotropical rocky fields. These microsatellite loci will be used to investigate population differentiation and species cohesion in such fragmented environments. The loci were tested for cross-amplification in related bromeliad species.Methods and Results: Eleven polymorphic microsatellite markers were isolated and characterized from an enriched library of O. ophiuroides. The loci were tested on 42 individuals from two populations of this species. The number of alleles per locus ranged from three to nine and the expected and observed heterozygosities ranged from 0.167 to 0.870 and from 0.369 to 0.958, respectively. Seven loci successfully amplified in other related bromeliad species.Conclusions: Our results suggest that the microsatellite loci developed here will be useful to assess genetic diversity and gene flow in O. ophiuroides for the investigation of population differentiation and species cohesion in neotropical mountainous habitats.
Keywords: Bromeliaceae; cross-amplification; gene flow; genetic diversity; Orthophytum ophiuroides; population genetics